A fisioterapia respiratória é eficaz na redução do escore clínico em lactentes com bronquiolite viral aguda: ensaio clínico randomizado - Gomes, Évelim Leal de Freitas Dantas (2010)
Objective: To evaluate the effectiveness of chest physiotherapy (CP) in reducing the clinical score in infants with acute viral bronchiolitis (AVB). Methods: Randomized clinical trial of 30 previously healthy infants (mean age 4, 08  3, 0 months) with AVB and positive for respiratory syncytial virus (RSV), evaluated at three moments: at admission, then at 48 and 72 hours after admission. The procedures were conducted by assessors blind to each of three groups: G1 New chest physiotherapy- nCPT (Prolonged slow expiration-PSE and Clearance rhinopharyngeal retrograde - CRR), G2 - Conventional chest physiotherapy- cCPT (modified postural drainage, expiratory compression, vibration and percussion) and G3 - aspiration of the upper airways through the Wang s clinical score (CS) and its components: Retractions (RE), respiratory rate (RR), Wheezing (WH) and General Conditions (GC). Results: The CS on admission was reduced in G1 (7.0 - 4.0) and G2 (7.5 - 5.5) but was unchanged in G3 (7.5 to 7.0). In the 48 hours after hospitalization, there was a change in G1 (5.5 - 3.0) and G2 (4.0 - 2.0) and in 72 hours, there was a change in G1 (2.0 - 1.0). Conclusion: The CP was effective in reducing the CS in infants with AVB compared with upper airway suction only. After 48 hours of admission, both techniques were effective and nCPT techniques were also effective in the 72 hours after hospitalization compared with cCPT techniques.